HUBUNGAN PEMAHAMAN MATERI HAK DAN KEWAJIBAN DENGAN SIKAP TANGGUNG JAWAB PESERTA DIDIK KELAS IV SEKOLAH DASAR DI KECAMATAN JAGAKARSA - Aryanti, Anis Tri; Zakiah, Linda; Yarmi, Gusti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The direction of this study was carried out to find out there is a relationship between the understanding of rights and duties material with the attitude of responsibility of fourth-grade students in elementary schools in Jagakarsa District for the academic year 2023–2024. A quantitative correlational method with an ex post facto design was utilized in this research at SDN Tanjung Barat 07, SDN Ciganjur 01, SDN Srengseng Sawah 17, and SDN Ciganjur 04 from January to June. The correlation coefficient obtained was 0.514, supporting the hypothesis that there is a relationship understanding of rights and duties material and student’s sense of responsibility at a significance level of α = 0.05. Due to the positive correlation coefficient, it can be concluded that the understanding of rights and duties material is positively correlated with the students' sense of responsibility. The coefficient of determination (r2) has the results of the test of 26.41%, indicating that the remaining 73.59% is explained by other unexamined variables.